Production of thermoplastic starch-aloe vera gel film embedded with polyethylene for improved tensile strength and water absorption / Siti Fatma Abd Karim ... [et al.] - Abd Karim, Siti Fatma; Jai, Junaidah; Abdol Aziz, Rabiatul Adawiyah; Maqsood-Ul-Haque, Siti Noor Suzila; Ku Hamid, Ku Halim; Mulana, Farid (UiTM Press, 2024)
The water absorption characteristics of thermoplastic starch (TPS) reveal its ability to interact with and absorb water, influencing its overall performance in various applications. The introduction of aloe vera (AV) gel into the TPS polymeric matrix film has proven beneficial in enhancing tensile strength but a notable deficiency is observed in lowering water absorption percentage. Therefore, this paper aims to reduce the water absorption of the TPS30AV polymer matrix film by utilizing polyethylene (PE) without reducing the tensile strength performance of the TPS30AV film. The TPS30AV film was produced using melt-blending and hot-press techniques. Six samples were presented consisting of a control film (TPS30AV) and TPS30AV film with different concentrations of PE resins (5%, 10%, 20%, 30%, and 40%). The film's performance was assessed by examining its mechanical properties, water absorption, and water solubility. The finding shows that TPS30AV with 40% PE has the highest improvement in water absorption percentage which reduces from 309.86% to 34.16% but a tremendous decrement in tensile strength performance. However, TPS30AV with 10% PE has the highest tensile strength, 9.65 MPa with a 20.99% improvement in water absorption reduction. The properties obtained for TPS30AV10PE were also good in Young's modulus and water solubility percentage. It shows that the film formulated is comparable with previous studies, and improvement has been achieved. As a conclusion, adding PE improved the polymeric structure of TPS30AV and can be used as a biodegradable food-packaging film.